2004
DOI: 10.1046/j.0767-3981.2003.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine kidney distribution in male rats following a single intraperitoneal dose

Abstract: As it has been previously shown that lamotrigine (LTG) accumulates in the kidney of male rats, the purpose of the present investigation was to characterize the kidney profiles of LTG and its kidney distribution pattern in male rats, in order to confirm if a preferential distribution exists and to analyse if it does or does not affect the LTG systemic pharmacokinetics. Adult male Wistar rats were intraperitoneally injected with 5, 10 and 20 mg/kg of LTG. The concentration-time profiles of LTG in plasma and whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…In fact, the parallel decline of lamotrigine concentrations in the brain and those measured in plasma also suggests no excessive retention of the drug in the brain tissue, which is consistent with Parsons et al [25] when they state that the rate of lamotrigine elimination from tissues is comparable to that from plasma, with the exception of the kidney [26] and melanin-containing tissues. by the linear relationship established between drug in plasma and drug in brain after the plasma-brain equilibrium had been reached -it can be suggested that the distribution of lamotrigine from plasma into brain tissue is only limited by blood flow and that lamotrigine crosses the blood-brain barrier by simple diffusion.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In fact, the parallel decline of lamotrigine concentrations in the brain and those measured in plasma also suggests no excessive retention of the drug in the brain tissue, which is consistent with Parsons et al [25] when they state that the rate of lamotrigine elimination from tissues is comparable to that from plasma, with the exception of the kidney [26] and melanin-containing tissues. by the linear relationship established between drug in plasma and drug in brain after the plasma-brain equilibrium had been reached -it can be suggested that the distribution of lamotrigine from plasma into brain tissue is only limited by blood flow and that lamotrigine crosses the blood-brain barrier by simple diffusion.…”
Section: Discussionsupporting
confidence: 87%
“…by the linear relationship established between drug in plasma and drug in brain after the plasma-brain equilibrium had been reached -it can be suggested that the distribution of lamotrigine from plasma into brain tissue is only limited by blood flow and that lamotrigine crosses the blood-brain barrier by simple diffusion. In fact, the parallel decline of lamotrigine concentrations in the brain and those measured in plasma also suggests no excessive retention of the drug in the brain tissue, which is consistent with Parsons et al [25] when they state that the rate of lamotrigine elimination from tissues is comparable to that from plasma, with the exception of the kidney [26] and melanin-containing tissues. Taking into consideration these data, the brain cannot be considered as another pharmacokinetic compartment individualized from the central compartment, but can specifically be considered as a hypothetical effect compartment that is modelled as an additional compartment that represents the active drug concentration at the effect site [24].…”
Section: Discussionsupporting
confidence: 87%
“…The therapeutic range for phenytoin plasma levels in the human is 10 to 20μg/ml37; the dose of phenytoin selected (50mg/kg) results in peak plasma levels of 35μg/ml, with sustained plasma levels of 10μg/ml for at least 4 hours 13. In patients, plasma levels of lamotrigine have between reported between 1.8 and 11.1μg/ml38; the dose of lamotrigine (20mg/kg) was selected to result in plasma levels in the rat between 8 and 12μg/ml 39, 40. Moreover, cerebrospinal fluid (CSF) levels of lamotrigine in patients reach 3.4 to 3.6μg/ml38; 20mg/kg of lamotrigine in rats results in CSF levels between 2.6 and 5μg/ml 40.…”
Section: Methodsmentioning
confidence: 99%
“…13 In patients, plasma levels of lamotrigine have between reported between 1.8 and 11.1lg/ml 38 ; the dose of lamotrigine (20mg/ kg) was selected to result in plasma levels in the rat between 8 and 12lg/ml. 39,40 Moreover, cerebrospinal fluid (CSF) levels of lamotrigine in patients reach 3.4 to 3.6lg/ml 38 ; 20mg/kg of lamotrigine in rats results in CSF levels between 2.6 and 5lg/ ml. 40 The doses of phenobarbital and phenytoin selected produce cell death in neonatal rats, whereas the dose of lamotrigine selected is less than half the dose required to produce cell death.…”
Section: Relevance Of Doses Used To Human Drug Levelsmentioning
confidence: 99%